Trajectory Tracking with Input Constraint based on LMI Approach of a Nonholonomic Mobile Robot - Auliya Nabila; Trihastuti Agustinah (JAREE (Journal on Advanced Research in Electrical Engineering), 2021)
Nonholonomic Mobile Robot (NMR) is a mode of transportation that is widely used in industry. To achieve flexibility in carrying out its duties, an adequate control system is needed in transportation arrangements so that it is used as an object of research. The problem that is taken in this study is about tracking control for several reference trajectories with input constraint. To solve this problem two controllers were designed, kinematics controller and dynamics controller. Kinematics controller is designed so that the additional speed converges to the desired speed by adjusting the gain value. Dynamic controller is designed using  performance to overcome the input constraint and the Lyapunoc inequality is soleved by Linear Matric Inequalities (LMI) so the gain state-feedback can be obtained. Simulation results show that the designed controller is capable of tracking according to the reference trajectory with input constraint given.Keywords: ????∞ performance, input constraint, linear matrix inequalities, NMR.